Detection of Formalin Content in Chicken Meat Using Portable Near Infrared Spectrometer - Agita Rakhmawati; Yohanes Aris Purwanto; Slamet Widodo; Dewi Apri Astuti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Food safety is essential for consumers. One of the compound that are prohibited from being used to preserve chicken meat is formalin. It demands a fast classification and sorting process for chicken meat, whether it is processed further or not. The main objective of this research is to develop a model that can predict the formalin content of chicken meat at room temperature using a portable NIR spectrometer. The NIRS method utilizes electromagnetic waves in infrared radiation with wavelengths ranging from 740-1070 nm. The method used to process the data is partial least square discriminative analysis (PLS-DA) to determine the presence of formalin in chicken meat. The results showed that the best pre-treatment was using the 1st derivative which had calibration results with an accuracy value of 92.86%, sensitivity 94.05%, specificity 91.67%, and FPR 8.33%. While the validation results obtained an accuracy value of 92.86%, sensitivity 92.86%, specificity 92.86%, and FPR 7.14%. Keywords: Chicken meat, formalin, NIRS, non-destructive method, PLS-DA.